2014
DOI: 10.3390/medicines1010056
|View full text |Cite
|
Sign up to set email alerts
|

Acupoint Activation: Response in Microcirculation and the Role of Mast Cells

Abstract: Background: According to Traditional Chinese Medicine (TCM) theory, acupuncture effects are based on the integrity function of meridians. Meridians are thought to regulate body function through the normal flow of qi and/or blood. Disturbances in this flow are thought to cause disease, and acupuncture techniques are believed to cure disease by regulating this flow. However, it is still difficult to understand the exact meaning of qi and to evaluate the activation of meridians. Thus, more and more attention has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In the clinic, different temperatures might produce different moxibustion effects largely because of the activation of different subtypes of transient receptor potential (TRP) 29 , 30 . Because various subtypes of TRP are widely distributed on the surface of mast cells 31 , 32 , and the activation of mast cells directly regulates local blood flux 33 , 34 , the impact of different temperature stimulations on local blood flux is necessarily different, and the previous results have provided evidence to support this.…”
Section: Discussionmentioning
confidence: 92%
“…In the clinic, different temperatures might produce different moxibustion effects largely because of the activation of different subtypes of transient receptor potential (TRP) 29 , 30 . Because various subtypes of TRP are widely distributed on the surface of mast cells 31 , 32 , and the activation of mast cells directly regulates local blood flux 33 , 34 , the impact of different temperature stimulations on local blood flux is necessarily different, and the previous results have provided evidence to support this.…”
Section: Discussionmentioning
confidence: 92%
“…Regarding the possible mechanisms underlying an increase in the MCs recruitment and degranulation levels during acupoint sensitization, some studies have focused on the structure of the MCs, nerve fibers and blood vessels in the acupoint in order to understand possible interactions between the circulatory, nervous and immune system from a histological perspective [ 29 30 ]. In particular, adhesion molecules [ 31 ], angiogenic factors [ 32 ], lipid mediators [ 33 ], which upon expression in or release from the endothelial cells, have been reported capable of promoting recruitment of MCs.…”
Section: Discussionmentioning
confidence: 99%
“…AM is a therapeutic method based on the stimulation of human acupoints, meridians, and local foot reflection areas. It can improve microcirculation, relieve inflammation, and reduce the production of free radicals and maintain the dynamic balance of it . AM has similar mechanism to acupuncture and other acupoints and meridian‐based treatment in general .…”
Section: Discussionmentioning
confidence: 99%
“…As two important parts of the external treatment of traditional Chinese medicine (TCM), TCM foot bath (FB) and acupoint massage (AM) have been used over thousands of years in China, and scientific research has confirmed that TCM FB can promote microcirculation, improve skin permeability, and increase drug absorption. Meanwhile, AM can improve microcirculation, relieve inflammation, and reduce the production of free radicals and maintain the dynamic balance of it . However, the use of TCM FB combined with AM in the treatment of DPN in other countries is not popular and the clinical efficacy of TCM FB combined with AM plus other treatments such as WM and oral traditional Chinese medicine (OTCM) was not certain.…”
Section: Introductionmentioning
confidence: 99%